Size Distribution Measurements of Fine Particles Using Their Pearl Chain Formations under a DC Electric Field - Otsuki, Akira; Dodbiba, G.; Fujita, T. (John Wiley & Sons, Ltd, 2012)
This book bridges three different fields: nanoscience, bioscience, and environmental sciences. It starts with fundamental electrostatics at interfaces and includes a detailed description of fundamental theories dealing with electrical double layers around a charged particle, electrokinetics, and electrical double layer interaction between charged particles. The stated fundamentals are provided as the underpinnings of sections two, three, and four, which address electrokinetic phenomena that occur in nanoscience, bioscience, and environmental science. Applications in nanomaterials, fuel cells, electronic materials, biomaterials, stems cells, microbiology, water purification, and humic substances are discussed.